Islamic Character Education For The Millennial Generation: The Role Of Social Media And Information Technology - Reyhana, Reyhana; Azmiannur, Muhammad (Fakultas Hukum Dehasen, 2025)
This research aims to analyze the role of social media and information technology in Islamic character education for the millennial generation. Millennials who grow up in the digital era face great challenges in maintaining moral and moral values in accordance with Islamic teachings. Along with the rapid development of technology, social media emerged as a means that can be utilized to spread da'wah messages and form Islamic character. This research uses a qualitative approach with a case study design, through social media content analysis and in-depth interviews with da'wah leaders and social media users. The results show that social media, especially platforms such as YouTube, Instagram, and TikTok, have a significant role in spreading Islamic values. The da'wah content published on these platforms contains moral messages that focus on Islamic morals, worship, and daily life in accordance with Islamic principles. However, this study also found major challenges related to the large amount of negative content spread on social media, which can damage the morals and morals of the millennial generation.